PEMBERDAYAAN WANITA NELAYAN MELALUI DIVERSIFIKASI PRODUK PERIKANAN DI KOTA TERNATE - Mutmainnah Mutmainnah; Yuliana Yuliana; Martini Djamhur; Khamsiah Ahmad; Surahman Surahman (Jurnal Abdi Insani, 2023)
The Standard of living for fishermen’s families can be achieved through economic creativity by developing and diversifying fishery products. Women in fishery families have an essential contribution and an important role in their households. However, the part is not only domestically but also publicly, such as in marketing the products, refinement of the fishing gears, and fishing activities, among others. The object of the Community Service is mentoring activities and imparting knowledge through the diversification of fishery processing product with the fisherwomen (fishermen's wives and fisherman's daughters who do not have regular activities) as the targeted people. The activity was carried out in July 2022 at the Jambula KUB, Ternate City, North Maluku Province. Initial activities conducted were observation and discussion related to the desire and interest of fisherwomen to utilize fishery products to have added value through the process of fish catches. Results: The outputs that will result from this community service activity are (1) diversification of fish food products (local name : mpek=mpek and fish meatballs); (2) transferring of business management knowledge on how to make financial report for fishermen's families and (3) introducing the use digital media for business and marketing purposes and (4) the ability of fisherwomen to obtain other income from the small-scale fishery that has an impact on the family welfare, (5) Fishermen's family life is more prosperous and (6) scientific publications through reliable journals.